2005
DOI: 10.1093/jee/98.6.1839
|View full text |Cite
|
Sign up to set email alerts
|

Effective Control of a Field Population of Helicoverpa armigera by Using the Small RNA Virus Helicoverpa armigera Stunt Virus (Tetraviridae: Omegatetravirus)

Abstract: The first comprehensive field trial using an insect small RNA virus as a control agent on a cropping system was conducted with the Helicoverpa armigera stunt virus (family Tetraviridae, genus Omegatetravirus, HaSV). The virus was semipurified, quantified, and applied at two rates, 4 x 10(15) and 4 x 10(14) virus particles/ha, with minimal formulation on sorghum against the bollworm Helicoverpa armigera (Hübner). For comparison, a commercial preparation of Helicoverpa zea single-nucleopolyhedrovirus (HzSNPV, Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…However, several studies have reported that Bt-resistance has evolved in the field (Gunning et al, 2005;Zhang et al, 2012). Thus, other forms of biological pest control, including the use of host-specific viral pesticides, derived from baculovirus (Allaway and Payne, 1984;Chen et al, 2001;Fuxa, 2004;Sun et al, 2002;Sun et al, 2004), small RNA viruses (Christian et al, 2005) and densoviruses (El-Far et al, 2012), has attracted more attention from researchers. Moreover, high-through-put analytical methods such as metagenomics and RNA sequencing provide sensitive and effective methods for the discovery of novel viruses and asymptomatic disease agents that may be useful as biological control products (Diatchenko et al, 1996;Ge et al, 2012;Marguerat and Bähler, 2009;Mokili et al, 2012;Radford et al, 2012;Roossinck et al, 2015), or conversely, may negatively or positively impact upon the biopesticide products being used.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported that Bt-resistance has evolved in the field (Gunning et al, 2005;Zhang et al, 2012). Thus, other forms of biological pest control, including the use of host-specific viral pesticides, derived from baculovirus (Allaway and Payne, 1984;Chen et al, 2001;Fuxa, 2004;Sun et al, 2002;Sun et al, 2004), small RNA viruses (Christian et al, 2005) and densoviruses (El-Far et al, 2012), has attracted more attention from researchers. Moreover, high-through-put analytical methods such as metagenomics and RNA sequencing provide sensitive and effective methods for the discovery of novel viruses and asymptomatic disease agents that may be useful as biological control products (Diatchenko et al, 1996;Ge et al, 2012;Marguerat and Bähler, 2009;Mokili et al, 2012;Radford et al, 2012;Roossinck et al, 2015), or conversely, may negatively or positively impact upon the biopesticide products being used.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the introduction of Bt-cotton in the 1990s has seen a dramatic decline in the H. armigera moth population. However, there are signs of Bt-resistance emerging [23], [24], fueling renewed interest in other forms of biological pest control, including the use of host-specific viral pesticides, derived from densoviruses [25], small RNA viruses [26] and baculoviruses [27], [28], [29], [30], [31]. Previously, we reported a novel densovirus (HaDNV-1, from the family Parvoviridae) in H. armigera moths that possesses a monosense genome that is 4926 nucleotides in length and clustered with the members of the genus Iteravirus in phylogenetic analysis [32].…”
Section: Introductionmentioning
confidence: 99%
“…Here we describe the construction of a full-length clone of the RNA genome of Rhopalosiphum padi virus (RhPV) and baculovirusmediated expression of the clone to produce virions that are infectious to aphids. This study suggests that baculovirus vectors may be useful for the production of SRV biopesticides (11,12,30,42).…”
mentioning
confidence: 82%
“…There are several examples of the use of SRVs for insect pest control (11,42), including the use of Cricket paralysis virus for control of the olive fruit fly (30) and Helicoverpa armigera stunt virus (Tetraviridae) for control of H. armigera (12). Baculovirus expression of infectious clones of SRV provides an alternative approach to the production of viruses such as H. armigera stunt virus, for which susceptible cell lines have not been identified.…”
Section: Baculovirus-mediated Rhpv Expression In Sf21 Cellsmentioning
confidence: 99%